Penataan ruang kota Jakarta Pusat berbasis kualitas air tanah untuk perkotaan berkelanjutan - Mustafa, Annisa Fitri (Institute for Advanced Science Social, and Sustainable Future, 2024)
The rapid development and urbanization process in urban areas have exerted significant pressure on the groundwater quality of urban areas. The objective of this paper is to spatially analyze the groundwater quality in Central Jakarta and its relationship with urban spatial planning and land use. The approach taken in this paper is quantitative, involving the collection of secondary data and spatial and descriptive data analysis. Groundwater quality parameters include color, turbidity, iron (Fe), mercury, cadmium, hardness (CaCO3), hexavalent chromium, nitrate, nitrite, zinc (Zn), sulfate, lead (Pb), manganese (Mn), detergents, organic (KMnO4), total coliform, E. Coli, Florida, and pH. The analysis results indicate that the land use in Central Jakarta is predominantly residential, with the dominant critical parameter affecting groundwater quality being detergents. Based on the analysis of land use and observed critical parameters, anthropogenic factors, particularly residential activities, are identified as the most dominant factor contributing to the decline in groundwater quality in Central Jakarta.